The Impact of the Implementation of the Independent Curriculum on PAI Learning at SD Negeri 10 Lebong - Devi Purnama Sari; Eka Yanuarti; Aini Syahira Jamaluddin (CV Media Inti Teknologi, 2024)
Since the Independent Curriculum is a new curriculum that is currently being implemented, more research is required to determine how it affects PAI learning in elementary schools. The purpose of this study is to investigate how PAI learning at SD N 10 Lebong has been affected by the adoption of the Independent Curriculum. The research subject for this study is the principal and PAI teacher at SD N 10 Lebong, and it employs a descriptive qualitative methodology. Utilizing interviews, documentation, and observational data collection. The study's findings demonstrate that the initial installation of the Independent Curriculum at SDN 10 Lebong was successful in fostering a more vibrant and welcoming classroom. The flexibility provided by this curriculum allows teachers to adopt a variety of innovative teaching methods, such as the use of technology and project-based learning. Second, the students' enthusiasm and drive to master PAI courses has significantly improved after SDN 10 Lebong adopted the Independent Curriculum. Thus, it can be concluded that there is a flexibility of the curriculum that allows teachers to adopt more creative and interactive teaching methods, increasing student engagement and enthusiasm in learning.